Identification of DNA Corpse in Ordo Diptera Familia Calliphoridae Larvae in CSF1PO, TH01, and TPOX Locus Using Polymerase Chain Reaction (PCR) Methods - Tutik Purwanti1 , Ahmad Yudianto1 , Mochammad Soekry Erfan Kusuma1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Biomolecular techniques using DNA are known to have high accuracy in the identification ofdecaying bodies. In the process of identification, larvae found in corpses that have undergone decay can beused as alternative biological evidence to estimate the time of death.Aim: To identify the transfer of body DNA to the larvae of the fly ordo Diptera family Calliphoridae and theprocess of DNA transfer of decomposed bodies.Method: blood from the postmortem corpse was taken as a control, then soft tissue was taken as adecomposition product for the breeding of Dipdo family Calliphoridae larvae. The protocol used is DNAprofiling using the Short Tandem Repeat (STR) locus such as CSF1PO, TH01, and TPOX. The results ofDNA extraction from the postmortem body and DNA extraction results obtained from the skin of the larvaeand the digestive system of the larvae are then matched.Result: The results of this study found that there was DNA transfer in larvae proved by the matching ofDNA at the STR loci on the skin and the digestive system of larvae with the STR locus in blood taken fromthe postmortem bodyConclusion: the presence of decomposed corpse DNA decomposition to the larvae of members of the ordercalled Calliphorideae family which can be detected through the results of nuclear DNA visualization at theCSF1PO, TPOX, and TH01 loci using the PCR method